Effects of mobile devices on K–12 students' achievement: a meta‐analysis - Tingir, S.; Cavlazoglu, B.; Caliskan, O.; Koklu, O.; Intepe‐Tingir, S. (Journal of computer assisted learning, 2017)
In this meta‐analytic study, we investigated the effects of mobile devices on student achievement in science, mathematics and reading in grades K–12. Based on our inclusion criteria, we searched the ERIC and PsycINFO databases and identified 14 peer‐reviewed research articles published between 2010 and 2014. We identified the device type, subject area, intervention language, grade level, study design and implementer (i.e., of the intervention) as potential moderator variables that may influence student achievement in the targeted content areas. We followed a three‐level meta‐analytic procedure to estimate the overall effect of these variables and explain the variation in outcomes. The results suggest that use of mobile devices in teaching yielded higher achievement scores than traditional teaching in all subject areas. With regard to the analysis of moderator variables, the results suggest that using mobile devices in reading is significantly more effective than doing so in mathematics. Lay Description What is already known about this topic The use of mobile devices for educational purposes has become a new research area because mobile technology offers new opportunities for student learning, engagement and motivation. The rapid growth of mobile technology has influenced traditional practices in a number of areas such as communication, education and digital games. In mobile device research, the more frequently studied populations have been students in higher education as compared to K–12 students. Researchers found positive effects of mobile devices on student achievement in various subject areas. What this paper adds Reading subject scores are higher than those of mathematics subject for those students who used mobile devices in the classrooms. Achievement scores are not affected the by the use of mobile device, study language, grade level, study design and implementer. The design of the reading applications in mobile devices has the potential of improving student achievement. Implications for practice and/or policy Even though this meta‐analysis suggested higher achievement scores for the reading subject area, the other subject areas have the potential to improve achievement scores if the study is carefully designed. Introduction of diverse technologies has the potential to keep students more engaged in classroom practices through a variety of technological devices. More studies are needed that go beyond mere comparison of technology versus nontechnology interventions.